PENGARUH GOOD GOVERNANCE TERHADAP AKUNTABILITAS PELAYANAN DI RUMAH SAKIT UMUM DAERAH KOTA MAKASSAR TAHUN 2022 - Putri Megawati; Dian Ekawaty; Darmawati Junus; Mohammad Ardani Samad (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2024)
Good Governance is a concept of good governance and tolerance for public sector development. The type of research used is a quantitative descriptive survey with a Cross Sectional Study model. This research was conducted with a sample of 89 respondents. The data of this research were taken through questionnaires and direct observation and the data analysis technique used multiple linear regression test with the help of SPSS. The results of this study indicate that the assessment of the Good Governance variable obtained a value of sig = 0.041 <0.05. Transparency variable obtained sig value = 0.001> 0.05. Justice variable obtained sig value = 0.448 <0.05. the performance variable obtained sig = 0.037>0.05. The conclusion in this study is that Good Governance, Transparency and Performance have a significant influence on service accountability and it is recommended for hospital management to pay more attention to adequate facilities or equipment for employees or employees at the hospital.